NUMERICAL MODELING OF A ROCKSLIDE AVALANCHE AT KORYAKSKIY VOLCANO, KAMCHATKA - Adushkin V.V.; Zykov Yu.N.; Ivanov B.A. (My University, 1996)
A numerical model is proposed for the mechanism of a rockslide avalanche on the slope of Koryakskiy volcano caused by the emplacement of sheeted intrusive bodies. The model of non-stationary geomechanical processes with abnormally low internal friction is used to calculate an avalanchelike movement during a potential collapse of the cone.